Variants of the Aggression-Related RBFOX1 Gene in a Population Representative Birth Cohort Study: Aggressiveness, Personality, and Alcohol Use Disorder - Vaht, Mariliis; Laas, Kariina; Fernàndez-Castillo, Noèlia; Kurrikoff, Triin; Kanarik, Margus; Faraone, Stephen V.; Tooding, Liina-Mai; Veidebaum, Toomas; Franke, Barbara; Reif, Andreas; Cormand, Bru; Harro, Jaanus (Frontiers in Psychiatry, 2020)
Background Recently RBFOX1, a gene encoding an RNA binding protein, has consistently been associated with aggressive and antisocial behaviour. Several loci in the gene have been nominally associated with aggression in genome-wide association studies; the risk alleles being more frequent in general population. We have hence examined the association of four RBFOX1 single nucleotide polymorphisms, previously found related to aggressive traits, with aggressiveness, personality, and alcohol use disorder in birth cohort representative samples. Methods We used both birth cohorts of the Estonian Children Personality Behaviour and Health Study (ECPBHS; original n=1,238). Aggressiveness was assessed using the Buss-Perry Aggression Questionnaire and the Lifetime History of Aggressiveness structured interview at age 25 (younger cohort) or 33 (older cohort). Big Five personality at age 25 was measured with self-reports and the lifetime occurrence of alcohol use disorder assessed with the MINI interview. RBFOX1 polymorphisms rs809682, rs8062784, rs12921846 and rs6500744 were genotyped in all participants. Given the restricted size of the sample, correction for multiple comparisons was not applied. Results Aggressiveness was not significantly associated with RBFOX1 genotype. RBFOX1 rs8062784 was associated with neuroticism and rs809682 with extraversion. Two out of four analyzed RBFOX1 variants, rs8062784, and rs12921846, were associated with occurrence of alcohol use disorder. Conclusions In the birth cohort representative sample of the ECPBHS, no association of RBFOX1 with aggressiveness was found, but RBFOX1 variants affected basic personality traits and the prevalence of alcohol use disorder. Future studies on RBFOX1 should consider the moderating role of personality and alcohol use patterns in aggressiveness.